(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research addresses the critical issue of food security in developing countries through the lens of Artificial Intelligence (AI), with a focus on advanced deep learning techniques. Given the complexity and multifaceted nature of food security challenges, this study proposes the use of Convolutional Neural Networks (CNNs), a powerful deep learning tool known for its efficacy in processing and analyzing large-scale and diverse data sets.